Charged-particle multiplicities in proton–proton collisions at √s=0.9 to 8 TeV - Adam, J.; Adamovã, D.; Aggarwal, M.M.; Aglieri Rinella, G.; Agnello, M.; Agrawal, N.; Ahammed, Z.; Ahmed, I.; Ahn, S.U.; Aiola, S.; Akindinov, A.; Alam, S.N.; et al. (Springer Science and Business Media, LLC, 2017)
A detailed study of pseudorapidity densities and multiplicity distributions of primary charged particles produced in proton–proton collisions, at √s = 0.9, 2.36, 2.76, 7 and 8 TeV, in the pseudorapidity range |η| < 2, was carried out using the ALICE detector. Measurements were obtained for three event classes: inelastic, non-single diffractive and events with at least one charged particle in the pseudorapidity interval |η| < 1. The use of an improved track-counting algorithm combined with ALICE’s measurements of diffractive processes allows a higher precision compared to our previous publications. A KNO scaling study was performed in the pseudorapidity intervals |η| < 0.5, 1.0 and 1.5. The data are compared to other experimental results and to models as implemented in Monte Carlo event generators PHOJET and recent tunes of PYTHIA6, PYTHIA8 and EPOS.
Keywords: Pseudorapidity; Physics; Multiplicity (mathematics); Charged particle; Proton; Nuclear physics; Monte Carlo method; Range (aeronautics); Scaling; Particle physics; Event (particle physics); Ion; Statistics; Mathematics; Geometry; Materials science; https://purl.org/pe-repo/ocde/ford#1.03.04